The Dilemma of Scheme and Reality in Sociological Theory - Balon, Jan (Teorie vědy / Theory of Science, 2009)
The idea of conceptual scheme is clearly present in the classical and modern sociological theory. However, contemporary sociological thinking is highly critical of it and in its radical versions this idea is dismissed altogether. This article traces various historically formed insights into the nature of concept formation in sociology and tries to demonstrate that without the attempts at creating a coherent conceptual scheme, sociology would be deprived of any possibility to push through a specifically sociological perspective on the social world. Talcott Parsons’ conceptual level of theory is examined in detail and taken as an example of a viable theoretical approach based on the transformation of sociological concepts. The account of the sociological dilemma of scheme and reality is brought together with Donald Davidson’s argument against the dogma of scheme and reality. The idea of a conceptual scheme has been discredited in contemporary thinking together with the idea and the project of (grand) general theory of society. It is argued that from the generalizing critique of the idea of general theory it does not follow that sociology does not need sound concepts. If it were so then no sociological knowledge that would not refer only to itself would be possible.